Evaluasi Penerapan Good Corporate Governance (GCG) Pada PT Asuransi Jiwasraya (Persero) Medan - Simbolon, Lastrida; Muda, Indra; Batubara, Beby Masitho (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
This research aims to carry out an in-depth evaluation of the implementation of GCG at PT Asuransi Jiwasraya Medan, as well as identifying obstacles that hinder the implementation of these principles. A descriptive approach with qualitative research methods was used by researchers in carrying out this research. The research results show that the implementation of Good Corporate Governance (GCG) at PT Asuransi Jiwasraya (Persero) Medan still faces obstacles such as lack of transparency, accountability and problems of collusion, corruption and nepotism (KKN) at the director level. Weak supervision and lack of commitment from commissioners and the GMS also hinder the optimal implementation of GCG. Delays in payment of customer claims worsen the company's image. To improve governance and restore public trust, increased commitment is needed, eradicating KKN practices, as well as improvements in supervision and transparency.